Transpressional tectonics and strain partitioning during oblique collision between three plates in the Precambrian of southeast Brazil - Ebert, Hans Dirk [UNESP]; Hasui, Yociteru [UNESP] (Geological Society of London, 1998)
This paper is part of the special publication Continental transpressional and transtensional tectonics (eds R.E. Holdsworth, R.A. Strachan and J.F. Dewey). Two orogenic belts have been recognized in south- east Brazil, which are interpreted to have been formed as a product of diachronous collisions between three continental plates. Wide crustal-scale shear belts have developed both between and inboard of the collided and amalgamated plate borders. These shear belts record frontal, oblique or lateral displacements during oblique plate convergence and A-type subduction. The overall structural style of each belt depends on the angle subtended between the plate boundary and the convergence vector. The E-W branch between the Sao Paulo and Brasilia plates the Campo do Meio strike-slip shear belt, has undergone dominantly sinistral wrench dominated transpression along a set of folds and shear zones dipping southwards. The NE-SW branch between the Sao Paulo and Vitoria plates, the Paraiba do Sul strike-slip shear belt, has undergone a partitioned dextral transpression, whereas the north-south branch between the Brasilia and Vitoria plates is essentially a frontal thrust system with only a weak component of dextral strike-slip. These complex structural patterns, formed at deep to mid-crustal levels, reflect temporal and spatial partitioning at all scales between flattening and non- coaxial deformation, and down-dip and strike-slip shearing, in tangential as well as in transcurrent structural domains. Additionally, this area demonstrates that regional flower structures, lateral extrusion and other secondary deformations across the yz sections of transpressional belts are important in accommodating shortening in obliquely convergent orogens.
Keywords: continental collision; plate convergence; Precambrian; strain partitioning; transpression; Brazil